Is the data on your wearable device secure? An Android Wear smartwatch case study. (18th May 2016) - Do, Quang; Martini, Ben; Choo, Kim‐Kwang Raymond
Summary: The increasing convergence of wearable technologies and cloud services in applications, such as health care, could result in new attack vectors for the 'Cloud of Things', which could in turn be exploited to exfiltrate sensitive user data. In this paper, we analyze the types of sensitive user data that may be present on a wearable device and develop a method to demonstrate that they can be exfiltrated by an adversary. To undertake this study, we select the Android Wear smartwatch operating system as a case study and, specifically, the Samsung Gear Live smartwatch. We present a technique that allows an adversary to exfiltrate data from smartwatches. Using this technique, we determine that the smartwatch stores a relatively large amount of sensitive user data, including SMS messages, contact information, and biomedical data, and does not effectively protect this user data from physical exfiltration. Copyright © 2016 John Wiley & Sons, Ltd.